A solid-liquid composite super-slip carbon-based coating on rubber surface and preparation method thereof
By depositing Ta-C films on the rubber surface and building micro-pots, spraying polymer-coated nano-microcapsules and two-dimensional material nanosheets to form solid-liquid composite ultra-sliding carbon-based coatings, the problem of high friction coefficient of the rubber surface carbon film in the prior art is solved, and the ultra-sliding characteristics of the rubber surface and the long life of the seal are achieved.
Patent Information
- Application Number
- CN202310688021.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-06-12
AI Technical Summary
The friction coefficient of existing rubber surface carbon films is still high, and it is difficult to essentially solve the wear and failure problem of rubber sealing materials.
Magneto-controlled sputtering technology is used to deposit Ta-C films on the surface of the rubber substrate, and a micro-pot hole is constructed on the surface of the film by laser etching. Nano-microcapsules with polymer-coated lubricating oil are sprayed into the potholes, and finally two-dimensional material nanosheets are sprayed on the entire surface to form a solid-liquid composite ultra-sliding carbon-based coating.
It significantly reduces the film friction interface adhesion effect, realizes the ultra-slip characteristics of the rubber surface, effectively extends the service life of the seal, and maintains stability and durability under a variety of complex working conditions.
Smart Images

Figure CN116651716B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid-liquid composite super-lubricating carbon-based coating on a rubber surface and a preparation method thereof, and in particular to the construction of a Ta-C film / embedded polymer-coated lubricating oil nano-microcapsule / two-dimensional material nanosheet solid-liquid composite super-lubricating coating for the preparation of movable seals, belonging to the field of solid lubricating materials and tribology. Background Art
[0002] Seal failure is one of the key common technical problems of mechanical equipment sealing systems. When rubber and metal are matched, the friction coefficient is extremely high (µ>1). The friction heat generated by high friction can easily cause the rubber seal to soften and quickly wear out and fail, causing the high-pressure sealing medium to leak from the damaged part and fail to seal, affecting the safe and reliable service of the equipment. Therefore, solving the problem of rubber seal wear failure must start with reducing friction.
[0003] Carbon film has excellent properties such as low adhesion to steel, low deposition temperature (deposition temperature ≤ 100°C, which will not cause fatal damage to the nitrile rubber matrix), controllable composition and mechanical strength, variable structure (such as multi-micro-nano structure, multi-element doping, etc.), low friction and wear, etc., making it an ideal coating for achieving low friction on rubber surfaces. Although traditional carbon film can effectively reduce the friction of rubber, the friction coefficient is still high (≥0.2), which makes it difficult to fundamentally solve the wear failure problem of rubber sealing materials.
[0004] The friction of carbon film on rubber surface mainly includes adhesion friction and hysteresis friction. Adhesion friction comes from the continuous formation and destruction of adhesion points between rubber and the counter surface, and hysteresis friction comes from the hysteresis phenomenon of rubber stretching away from the hard surface when sliding relative to the hard surface. However, during the friction process, the friction coefficient of the film gradually increases, but its hysteresis friction effect gradually weakens, which shows that the friction coefficient of carbon film on rubber surface mainly depends on the adhesion effect of the friction interface. Therefore, how to reduce the adhesion effect of the film friction interface is the key to achieving the super-slip properties of rubber seals. Summary of the invention
[0005] The purpose of the present invention is to address the defect that the friction coefficient of existing carbon films on rubber surfaces is still relatively high, and to provide a carbon-based composite coating that can achieve super-slip properties on the rubber surface from the perspective of reducing the adhesion effect of the film friction interface.
[0006] 1. Preparation of solid-liquid composite super-slip carbon-based coating on rubber surface
[0007] The solid-liquid composite ultra-smooth carbon-based coating of the present invention is obtained by depositing a Ta-C film on the surface of a rubber substrate using magnetron sputtering technology, then constructing micron-pits on the surface of the film using laser etching, spraying polymer-coated nano-capsules of lubricating oil into the micron-pits, and finally spraying two-dimensional material nanosheets on the entire surface.
[0008] The rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, EPDM rubber and silicone rubber, and has a surface roughness of ≤150nm and a thickness of 1-3mm.
[0009] The carbon-based film is a hydrogen-free Ta-C film. The preparation method of the micron pits is a laser etching method, and the laser used in the laser etching method is an ultrashort pulse laser; the micron pit structure includes a circular ring structure, a criss-cross structure or a lattice distribution structure.
[0010] The nanometer microcapsules of the polymer-coated lubricating oil have a particle size of 200-300 nm and a wall thickness of 50-80 nm.
[0011] The method for preparing the polymer-coated lubricating oil nano-microcapsules comprises the following steps:
[0012] ① Add diisocyanate to liquid lubricant and stir to obtain solution A, and add emulsifier to deionized water and stir to obtain solution B;
[0013] ② Under high-speed stirring conditions, slowly add solution A to solution B to emulsify and obtain a microemulsion, and add diamine at a constant temperature to react for a period of time. After the reaction is completed, wash repeatedly with ethanol and distilled water, and finally filter and dry to obtain polymer-coated lubricating oil nanocapsules;
[0014] In the step ①, the liquid lubricant is one of animal and plant lubricating oil, synthetic lubricating oil and ionic liquid; the emulsifier is one or more of OP-10, sodium dodecylbenzene sulfonate, gum arabic and Tween 20; the diisocyanate is one or more of diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), lysine diisocyanate (LDI) and isophorone diisocyanate (IPDI).
[0015] In the step ①, the concentration of diisocyanate in solution A is 0.5-1.0 mol / L; the concentration of emulsifier in solution B is 0.3-0.5 g / ml;
[0016] In step ②, the diamine is one or more of triethylenediamine, hexamethylenediamine, and octanediamine; the volume ratio of solution A to solution B is 1:(4-8)-1:(20-25), the stirring speed is 7000-10000 rpm, and the emulsification time is 4-6 minutes; when adding the diamine, the temperature is 60-80°C, the stirring speed is 600-1000 rpm, and the reaction time is 2-4 hours.
[0017] The method for preparing a solid-liquid composite super-slip carbon-based coating on a rubber surface comprises the following steps:
[0018] (1) Substrate cleaning: The rubber substrate is cleaned with soapy water and high-temperature deionized water in an ultrasonic cleaning tank, then blown dry with nitrogen and placed in a coating vacuum chamber;
[0019] (2) Substrate bombardment pretreatment: The rubber substrate is bombarded with nitrogen plasma and argon plasma in turn; the conditions for nitrogen plasma bombardment are: nitrogen flow rate 200sccm, chamber pressure 4~6Pa, pulse bias voltage -700V, duty cycle 50~60%, frequency 60~70KHz; the conditions for argon plasma bombardment are: argon flow rate 300sccm, chamber pressure 4~6Pa, pulse bias voltage -1200V, duty cycle 50~60%, frequency 60~70KHz.
[0020] (3) Deposition of carbon film: using a graphite target, adjusting the target-substrate distance to 8-12 cm, the target current to 3 A, the argon flow rate to 45-60 sccm, the substrate bias to -700 V, the gas pressure to 1-1.5 Pa, the duty cycle to 40-45%, the frequency to 60-70 KHz, and the deposition time to 40-60 min;
[0021] (4) Thin film surface etching: A metal mask is pre-set on the thin film surface, and then an ultrashort pulse laser is used to etch the thin film surface to obtain micron-sized pits; preferably, the laser etching area of the thin film surface accounts for 20% to 30% of the total surface area, and more preferably 25%.
[0022] (5) Microcapsule spraying: The prepared nano-microcapsules are dissolved in an organic solvent and sprayed into the micron-sized pits using a portable sprayer, and then the metal mask is removed;
[0023] (6) Adding two-dimensional material nanosheets: dissolving the two-dimensional material nanosheets in a volatile solvent and spraying them onto the surface of the film using a portable sprayer. After the solvent is completely evaporated, the ultra-smooth carbon-based composite coating of the present invention can be obtained.
[0024] The two-dimensional material nanosheet is one or more of MXene-based, graphene-based and dichalcogenide transition metal-based two-dimensional materials.
[0025] Figure 1 This is a schematic diagram of the preparation process of the solid-liquid composite super-slip carbon-based coating on the rubber surface of the present invention; Figure 2The schematic diagram of the structure of the solid-liquid composite super-slip carbon-based lubricating coating on the rubber surface of the present invention. The outermost layer of the solid-liquid composite super-slip carbon-based coating designed by the present invention is a two-dimensional material nanosheet, and there are also micron-pits containing nano-capsules on the surface of the film. Under the action of friction contact stress, the nano-capsules in the micron-pits on the surface of the film can rupture to release lubricating oil, and cooperate with the surface two-dimensional material to achieve solid-liquid composite super-slip properties. At the same time, the micron-pits can be used as nano-capsule storage devices to continuously provide lubricating oil to the friction interface, ensuring the stability and durability of its super-slip properties.
[0026] 2. Evaluation of Friction Performance of Solid-Liquid Composite Super-Slippery Carbon-Based Coating on Rubber Surface
[0027] The tribological performance of the ultra-slip carbon-based composite coating of the present invention was evaluated using a friction and wear tester. The specific friction conditions are: ball-disc rotation mode, normal load 5-15N, friction pair φ6mm GCr15 steel ball, and test environment is atmospheric environment. The test results show that the friction coefficient of conventional carbon film is high (≥0.15), while the friction coefficient of the carbon-based composite coating of the present invention is significantly reduced (≤0.01), and can be used to prepare dynamic seals.
[0028] In summary, the present invention uses magnetron sputtering technology to deposit Ta-C film on the surface of the rubber substrate, and then uses laser etching to construct micron pits on the surface of the film, and sprays polymer-coated nano-microcapsules of lubricating oil into the pits, and finally sprays two-dimensional material nanosheets on the entire coating surface, thereby obtaining a solid-liquid composite super-slip carbon-based coating. The outermost layer of the coating is a two-dimensional material nanosheet, and there are also micron pits containing nano-microcapsules on the surface of the film. During the friction process, the nano-microcapsules in the micron pits on the surface of the film can break and release lubricating oil, and cooperate with the surface two-dimensional material to achieve solid-liquid composite super-slip properties. At the same time, the micron pits can be used as nano-microcapsule storage devices to continuously provide lubricating oil to the friction interface, ensuring the stability and durability of its super-slip properties; effectively reducing the adhesion effect of the film friction interface, overcoming the defect that the friction coefficient of the carbon film on the rubber surface is still high, and the super-slip property does not depend on the friction contact stress and the surrounding atmosphere environment, and can be applied to a variety of complex working conditions, and is easy to achieve large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention is a schematic diagram of the preparation process of the solid-liquid composite super-slip carbon-based coating on the rubber surface.
[0030] Figure 2 This is a schematic diagram of the structure of the solid-liquid composite super-slip carbon-based lubricating coating on the rubber surface of the present invention. DETAILED DESCRIPTION
[0031] The construction method and friction performance of the solid-liquid composite super-slip carbon-based lubricating coating on the rubber surface of the present invention are further described by specific examples below.
[0032] Example 1
[0033] (1) Cut a 300×300×2 mm black nitrile rubber sheet (surface finish Ra < 150 nm, thickness 2 mm) into 30×30 mm 2 The rubber sheet was soaked in a 60℃ soap solution for ultrasonic cleaning for 30 minutes to remove the grease and dirt on the rubber surface; then it was taken out and soaked in 90~95℃ distilled water for ultrasonic cleaning for 30 minutes to remove the possible residual soap solution; finally, it was blown dry with dry nitrogen and placed in a drying oven at 100℃ for another 20 minutes to evaporate the residual moisture on the rubber surface. The above process was repeated 5 times;
[0034] (2) After the rubber has cooled to room temperature, place it in a magnetron sputtering vacuum chamber. Close the vacuum chamber door and pump the vacuum to ≤1.0×10 –3 Pa. 200sccm nitrogen was introduced into the vacuum chamber, and the pressure in the chamber was 4Pa. The high-power pulse bias power supply was turned on, and the rubber was bombarded with nitrogen plasma, with a bias of -700V, a duty cycle of 55%, a frequency of 60KHz, and a treatment time of 35min. The nitrogen was then evacuated, and 300sccm argon was introduced, and the pulse bias was adjusted to -1200V. Other conditions remained unchanged and the bombardment cleaning was continued for 25min.
[0035] (3) After the bombardment, argon gas was immediately introduced, the graphite target sputtering power supply was turned on, the target-substrate distance was adjusted to 10 cm, the target current was 3 A, the argon gas flow rate was 45 sccm, the substrate bias was -700 V, the gas pressure was 1.0 Pa, the duty cycle was 40%, the frequency was 60 KHz, and the deposition time was 40 min; after the deposition was completed, the temperature in the vacuum chamber was cooled to room temperature and the sample was taken out for use;
[0036] (4) placing a metal mask with a circular ring structure on the surface of the sample in advance, and using an ultrashort pulse laser to etch circular ring-shaped micron pits on the surface of the sample for later use;
[0037] (5) Add 0.001 mol of isophorone diisocyanate to 2 mL of ionic liquid and mix well to obtain solution A. Add 3 g of emulsifier OP-10 to 10 mL of deionized water and stir well to form solution B.
[0038] (6) Slowly add the uniformly mixed solution A to solution B, and emulsify using a high-speed shear emulsifier at a speed of 7000 rpm for 5 minutes to form a microemulsion;
[0039] (7) Fix the flask containing the emulsion on a constant temperature magnetic stirrer, set the oil bath temperature to 60°C and the speed to 600 rpm. Add 0.004 mol of hexamethylenediamine and react for 2 h. After the reaction, wash repeatedly with ethanol and distilled water, and finally filter and dry to obtain polymer-encapsulated ionic liquid nanocapsules;
[0040] (8) Dissolve the above microcapsules evenly in ethanol, load them into a portable electric sprayer, and spray the coating surface. After the ethanol is completely evaporated, remove the metal mask and set aside;
[0041] (9) Dissolve the Ti3C2MXene nanosheets in an ethanol solution, load the solution into a portable electric sprayer, and spray the coating surface. After the ethanol is completely volatilized, the ultra-slip carbon-based composite coating sample of the present invention can be obtained. The friction coefficient of the carbon-based composite coating sample in the atmospheric environment is as low as 0.006.
[0042] Example 2
[0043] (1) Silicone rubber (surface finish Ra of silicone rubber is less than 100 nm and thickness is 3 mm) is used, and the pre-cleaning step is the same as that in Example 1;
[0044] (2) to (3) are the same as in Example 1;
[0045] (4) Pre-placing a metal mask with a diamond structure on the surface of the sample, and using an ultrashort pulse laser to etch diamond-shaped micron pits on the surface of the sample for later use;
[0046] (5) Add 0.002 mol of diphenylmethane diisocyanate into 2 mL of vegetable lubricating oil and mix well to obtain solution A. Add 2.5 g of emulsifier sodium dodecylbenzene sulfonate into 5 mL of deionized water and stir well to obtain solution B.
[0047] (6) Slowly add the uniformly mixed solution A to solution B, and emulsify using a high-speed shear emulsifier at a speed of 9000 rpm for 6 minutes to form a microemulsion;
[0048] (7) Fix the flask containing the microemulsion on a constant temperature magnetic stirrer, set the oil bath temperature to 80°C and the speed to 800 rpm. Add 0.004 mol of octanediamine and the reaction time is 3 h. After the reaction is completed, wash repeatedly with ethanol and distilled water, and finally filter and dry to obtain polymer-coated lubricating oil nanocapsules;
[0049] (8) Dissolve the above microcapsules evenly in ethanol, load them into a portable electric sprayer, and spray the coating surface. After the ethanol is completely evaporated, remove the metal mask and set aside;
[0050] (9) The graphene oxide nanosheets are dissolved in an ethanol solution, loaded into a portable electric sprayer, and sprayed on the coating surface. After the ethanol is completely volatilized, the ultra-slip carbon-based composite coating sample of the present invention can be obtained. The friction coefficient of the composite coating sample in the atmospheric environment is as low as 0.004.
Claims
1. A solid-liquid composite super-lubricating carbon-based coating on a rubber surface is obtained by depositing a carbon film on the surface of a rubber substrate using magnetron sputtering technology, then constructing micron-pits on the surface of the carbon film using laser etching, spraying polymer-coated nano-capsules of lubricating oil into the micron-pits, and finally spraying two-dimensional material nanosheets on the film surface; under the action of friction contact stress, the nano-capsules in the micron-pits on the film surface can rupture to release lubricating oil, and synergize with the surface two-dimensional material to achieve solid-liquid composite super-lubricating properties.
2. A solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 1, characterized in that: The rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, EPDM rubber and silicone rubber, and its surface roughness is ≤150nm and its thickness is 1-3mm.
3. A solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 1, characterized in that: The carbon film is a hydrogen-free Ta-C film.
4. A solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 1, characterized in that: The method for preparing the micron pits is laser etching, and the laser used in the laser etching method is an ultrashort pulse laser; the micron pit structure is one or more of a circular ring structure, a criss-cross structure, or a lattice distribution structure.
5. A solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 1, characterized in that: The particle size of the polymer-coated lubricating oil nano-microcapsule is 200-300 nm, and the wall thickness is 50-80 nm.
6. A method for preparing a super-slip carbon-based composite coating on a rubber surface as claimed in claim 1, characterized in that: (1) Substrate cleaning: The rubber substrate is cleaned with soapy water and high-temperature deionized water in an ultrasonic cleaning tank, then blown dry with nitrogen and placed in a coating vacuum chamber; (2) Substrate bombardment pretreatment: The rubber substrate is bombarded with nitrogen plasma and argon plasma in turn; the conditions for nitrogen plasma bombardment are: nitrogen flow rate 200sccm, chamber pressure 4~6Pa, pulse bias voltage -700V, duty cycle 50~60%, frequency 60~70KHz; the conditions for argon plasma bombardment are: argon flow rate 300sccm, chamber pressure 4~6Pa, pulse bias voltage -1200V, duty cycle 50~60%, frequency 60~70KHz; (3) Deposition of carbon film: using a graphite target, adjusting the target-substrate distance to 8-12 cm, the target current to 3 A, the argon flow rate to 45-60 sccm, the substrate bias to -700 V, the gas pressure to 1-1.5 Pa, the duty cycle to 40-45%, the frequency to 60-70 KHz, and the deposition time to 40-60 min; (4) Thin film surface etching: A metal mask is pre-set on the thin film surface, and then an ultrashort pulse laser is used to etch the thin film surface to obtain micron-sized pits; (5) Microcapsule spraying: The prepared nano-microcapsules are dissolved in an organic solvent and sprayed into the etched micron-sized pits using a portable sprayer, and then the metal mask is removed; The preparation of the nano-microcapsules comprises the following steps: ① Add diisocyanate to liquid lubricant and stir to obtain solution A, and add emulsifier to deionized water and stir to obtain solution B; ② Under high-speed stirring conditions, slowly add solution A to solution B to emulsify and form a microemulsion, and add diamine at 60-80°C and stir to react for 2-4 hours; after the reaction is completed, wash repeatedly with ethanol and distilled water, and finally filter and dry to obtain polymer-coated lubricating oil nanocapsules; (6) Adding two-dimensional material nanosheets: dissolve the two-dimensional material nanosheets in a volatile solvent and then spray them onto the surface of the film. After the solvent is completely evaporated, a solid-liquid composite ultra-smooth carbon-based coating can be obtained.
7. The method for preparing a solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 6, characterized in that: In step (5), the diisocyanate is one or more of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and isophorone diisocyanate, and the concentration in solution A is 0.5-1.0 mol / L; the liquid lubricant is one or more of animal and plant lubricating oils, synthetic lubricating oils, and ionic liquids; the emulsifier is one or more of OP-10, sodium dodecylbenzene sulfonate, gum arabic, and Tween 20, and the concentration in solution B is 0.3-0.5 g / mL.
8. The method for preparing a solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 6, characterized in that: In step (5), the volume ratio of solution A to solution B is 1:(4-8)-1:(20-25), the stirring speed is 7000-10000 rpm, and the emulsification time is 4-6 minutes; the diamine is one or more of triethylenediamine, hexamethylenediamine, and octanediamine, and the stirring speed during addition is 600-1000 rpm.
9. The method for preparing a solid-liquid composite super-slip carbon-based coating on a rubber surface as claimed in claim 6, characterized in that: In step (6), the two-dimensional material nanosheet is one or more of MXene-based, graphene-based and dichalcogenide transition metal-based two-dimensional materials.
Citation Information
Patent Citations
Ultralow-friction multi-layer composite carbon-based lubricating coating on rubber surface and construction method of ultralow-friction multi-layer composite carbon-based lubricating coating
CN113215525A
Method for obtaining a NANO capsule structure
US20150167146A1
Cited By
Solid-liquid composite super-lubricating coating based on self-assembled monomolecular film and preparation method of solid-liquid composite super-lubricating coating
CN118185459A
Solid-liquid composite superlubricity coating based on self-assembled monolayer and preparation method thereof
CN118185459B